Cloning and functional expression of alternative spliced variants of the ρ1 γ-aminobutyrate receptor - Martínez-Torres, Ataúlfo (The National Academy of Sciences, 1998)
The ρ1 γ-aminobutyrate receptor (GABA(ρ1)) is expressed predominantly in the retina and forms homomeric GABA-gated Cl(−) channels that are clearly different from the multisubunit GABA(A) receptors. In contrast to these, GABA(ρ1) receptors desensitize very little and are not blocked by bicuculline. In addition to GABA(ρ1), two new variants were identified in human retina cDNA libraries. Cloning and sequence analysis showed that both variants contain large deletions in the putative extracellular domain of the receptor. These deletions extend from a common 5′ site to different 3′ sites. The cDNA with the largest deletion, named GABA(ρ1)Δ450, contains a complete ORF identical to that of GABA(ρ1) but missing 450 nt. This cDNA encodes a protein of 323 aa, identical to the GABA(ρ1), but has a deletion of 150 aa in the amino-terminal extracellular domain. GABA(ρ1)Δ450 mRNA injected into Xenopus oocytes did not produce functional GABA receptors. The second GABA(ρ1) variant (GABA(ρ1)Δ51) contains a 51-nt deletion. In Xenopus oocytes, GABA(ρ1)Δ51 led to the expression of GABA receptors that had the essential GABA(ρ1) characteristics of low desensitization and bicuculline resistance. Therefore, alternative splicing increases the coding potential of this gene family expressed in the human retina, but the functional diversity created by the alternative spliced forms is still not understood.